QUALITY ASSESSMENT OF STUDENT COURSEWORKS: COMPETENCY-BASED APPROACH - T. M. Shamsutdinova (Образование и наука)
Introduction. Today, the issues of formation and assessment of professional competencies of students of the highest professional educational institutions are widely discussed in the scientific community. A large number of the Russian and foreign publications are devoted to the problems of competency-based approach. However, there is still no general technique for assessing a competency level formation as the characteristics of each program of training of specialists are so specific that it is impossible to build up a unified universal professional competency framework.The aim of the publication is to present the author’s methodology for assessing student courseworks in terms of the academic discipline “Databases” which is studied during a bachelor program “Business Informatics” based on the competency-based approach.Methodology and research methods. The research described in the publication is recognized as being empirical-exploratory and experimental. The content analysis of the Federal State Educational Standard of the Highest Education (FSES HE), the data mining technology and statistical methods of data processing were applied in the course of the present research. Results and scientific novelty. Taking into account the features of the competency-focused model of educational process and specifics of the field of vocational education, the criteria for assessing the quality of student courseworks are formulated. The relationship of these diagnostics criteria with the competencies stated in the educational standard is shown. This article demonstrates how it is possible to assess the general structure and separate sections of student courseworks using the means of the offered indicators. The following conclusions are drawn: 1) the system current control of professional competencies mastering is necessary for timely correcting of individual educational trajectories; 2) the assessment of professional competencies of students means diagnostics of preparation results including a large number of various criteria; 3) the unified approach to level formation measurement of professional competencies is impossible due to complexity and heterogeneity of their structure; 4) there is a need for the variability as well possibility of increase or reduction (association) of criteria for assessment of professional competencies in order to identify the most significant indicators of effectiveness and quality of a particular academic paper.Practical significance. The method provided enables to establish the relationship between contents of the training program and the requirements of FSES; to concretize assessment of competencies and to give reasons for its numerical indicators. Under a certain adaptation, this technique for assessment of student courseworks of economic and technical specialties can be applied for assessment of other academic works of students.